A review of ultra-thin ferroelectric films. (30th July 2021) - Yuan, Zi-lin; Sun, Yu; Wang, Dan; Chen, Ke-Qiu; Tang, Li-Ming
Abstract: Ultrathin ferroelectrics are of great technological interest for high-density electronics, particularly non-volatile memories and field-effect transistors. With the rapid development of micro-electronics technology, there is an urgent requirement for higher density electronic devices, which need ultra-thin ferroelectric materials films. However, as ferroelectric films have becomes thinner and thinner, electrical spontaneous polarization signals have been found in a few atomic layers or even monolayer structures. The mechanisms of detection and formation of these signals are not well understood and various controversial interpretations have emerged. In this review, we summarized the recent research progress in the ultra-thin film ferroelectric material, such as HfO2, CuInP2 S6, In2 Se3, MoTe2 and BaTiO3 . Various key aspects of ferroelectric materials are discussed, including crystal structure, ferroelectric mechanism, characterization, fabrication methods, applications, and future outlooks. We hope this review will offer ideas for further improvement of ferroelectric properties of ultra-thin films and promotes practical applications.